2005
DOI: 10.1074/jbc.m509071200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functional Phosphatidylinositol 3,4,5-Trisphosphate Binding Site in the Epithelial Na+ Channel

Abstract: Membrane phospholipids, such as phosphatidylinositol 3,4,5-trisphosphate (PI(3,4,5)P 3 ), are signaling molecules that can directly modulate the activity of ion channels, including the epithelial Na ؉ channel (ENaC). Whereas PI(3,4,5)P 3 directly activates ENaC, its binding site within the channel has not been identified. We identify here a region of ␥-mENaC just following the second trans-membrane domain (residues 569 -583) important to PI(3, Direct regulation of ion channel activity by phospholipid signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 49 publications
10
71
0
Order By: Relevance
“…ENaC, similar to some other types of ion channels, senses membrane phosphoinositide levels and responds with changes in channel P o through direct interactions with these molecules (see reference [27]). Our laboratory showed that ENaC physically interacts with the phosphoinositide products of PI3-K and that this interaction stabilizes ENaC gating to increase P o (24,26). These findings are consistent with such a mechanism contributing to regulation of ENaC activity in both the immortalized mouse principal cell line and principal cells from freshly isolated rat collecting ducts studied here.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…ENaC, similar to some other types of ion channels, senses membrane phosphoinositide levels and responds with changes in channel P o through direct interactions with these molecules (see reference [27]). Our laboratory showed that ENaC physically interacts with the phosphoinositide products of PI3-K and that this interaction stabilizes ENaC gating to increase P o (24,26). These findings are consistent with such a mechanism contributing to regulation of ENaC activity in both the immortalized mouse principal cell line and principal cells from freshly isolated rat collecting ducts studied here.…”
Section: Discussionsupporting
confidence: 78%
“…Again, segments before and after LY294002 are shown below at expanded time scales. The results in Figures 6 and 7 demonstrating that the P o of active ENaC within the apical membrane of native and cultured principal cells is tightly coupled to PI3-K activity are consistent with our previous findings in expression studies (24,26).…”
Section: Tight Spatiotemporal Coupling Between Pi3-k Signaling and Ensupporting
confidence: 80%
“…Binding of PIP 2 to both K ir 1 and K ir 6 channels promotes channel activation by stabilizing the open state (32)(33)(34), and PIP 3 has been proposed to activate both epithelial sodium channels and TRPC6 channels by direct binding (35,36). Like PIP 2 -binding regions identified in other ion channels (37)(38)(39), the stretch of amino acids between residues 61-90 of CNGA2 contains multiple basic residues that may be important for the interaction with negatively charged phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that glucocorticoid hormones do induce SGK1 expression (31), SGK1 is an important downstream target of PI3K (29), and data from several absorptive cell types have suggested that insulin can increase the apical abundance of ENaC via a mechanism dependent on a PI3K-mediated increase in SGK1 activity (2,8,46,51). Moreover, PIP 2 and PIP 3 also activate ENaC by binding to the channel complex, and this provides another mechanism by which PI3K-coupled agonists, such as insulin, can stimulate Na ϩ transport (20,42,43,52). However, although the present data show that insulin stimulation/PI3K-P110␣ expression can control G Cl , these maneuvers had no effect on G Na in hormonedeprived cells but augmented the dexamethasone/SGK1-induced G Na .…”
Section: Discussionmentioning
confidence: 99%